2007
DOI: 10.3108/beej.10.9
|View full text |Cite
|
Sign up to set email alerts
|

Realising e-Learning matters in a Bioscience Cohort

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Several studies also reported that engagement in e-learning among learners and professionals, mainly from HSE, is useful and has positively impacted engagement and retention of learning [50,58,63]. The extracts below illustrate this:…”
Section: Theme 4: Integration Of E-learning Into Curriculamentioning
confidence: 85%
“…Several studies also reported that engagement in e-learning among learners and professionals, mainly from HSE, is useful and has positively impacted engagement and retention of learning [50,58,63]. The extracts below illustrate this:…”
Section: Theme 4: Integration Of E-learning Into Curriculamentioning
confidence: 85%
“…Mature-entry students taking part in this study were less likely to seek pastoral support from university-based services; they were however, equally likely to seek support from their academic tutors. The reasons for this finding may include a lack of awareness of the pastoral services available, and they may feel less integrated in the university habitus (Parry et al 2007). Additionally, mature students may be less willing to approach university staff for support or may simply not have enough time to seek support in the face of multiple-off campus responsibilities.…”
Section: Familiaritymentioning
confidence: 88%
“…Other universities have adopted similarly proactive approaches to retention including student mentoring by more experienced peers (Devlin and Nicholson n.d.), academic mentors (Wilson 2002), 'quality teaching' (Lizzio, Wilson, and Simons 2002) departmental action plans, dedicated retention officers (Devlin and Nicholson n.d.) and training for academic staff (STAR Projects 2008), and 'learning communities' (Mangold et al 2002-03). Changes to the curriculum including the introduction of modular schemes, flexible learning locations and e-learning (Parry et al 2007), student-centred learning (Thomas and Crosling 2007), low stakes and formative assessment (Yorke 2001), collaborative learning (Tinto 1997) and manageable workload (Lizzio, Wilson, and Simons 2002) are all encouraged to enhance student achievement.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…E-Learning becomes more productive with the continuation of a traditional class combines with an online class. Furthermore, E-Learning has become a potential learning platform that provides access all the time where students will be able to learn anytime and anywhere from every corner of the universe [17]. There are some benefits that can be obtained by anyone who uses E-Learning as a learning medium [1].…”
Section: Introductionmentioning
confidence: 99%